Ethnicity, Inc., John L. Comaroff y Jean Comaroff - Llanes Salazar, Rodrigo (Alteridades, 2014)
Reseña del libro de John L. Comaroff y Jean Comaroff, Ethnicity, Inc., The University of Chicago Press, Chicago, 2009, 234 pp.